Aquaporins 6–12 in the human eye. (13th September 2012) - Tran, Thuy Linh; Bek, Toke; Holm, Lars; la Cour, Morten; Nielsen, Søren; Prause, Jan Ulrik; Rojek, Aleksandra; Hamann, Steffen; Heegaard, Steffen
Abstract. Purpose: Aquaporins (AQPs) are widely expressed and have diverse distribution patterns in the eye. AQPs 0–5 have been localized at the cellular level in human eyes. We investigated the presence of the more recently discovered AQPs 6–12 in the human eye. Methods: RT‐PCR was performed on fresh tissue from two human eyes divided into the cornea, corneal limbus, ciliary body and iris, lens, choroid, optic nerve, retina and sclera. Each structure was examined to detect the mRNA of AQPs 6–12. Twenty‐one human eyes were examined using immunohistochemical and immunofluorescence techniques to determine the topographical localization of AQPs 6–12. Results: mRNA transcripts of AQP7, AQP9 and AQP11 were found in the ciliary body, corneo‐limbal tissue, optic nerve, retina and sclera. AQP9 and AQP11 mRNA was also detected in the choroid. No mRNA of AQP6, AQP8, AQP10 or AQP12 was detected. Anti‐AQP7 immunolabelling was detected in the corneal epithelium, corneal endothelium, trabecular meshwork endothelium, ciliary epithelia, lens epithelium, the inner and outer limiting membrane of the retina, the retinal pigment epithelium and the capillary endothelium of all parts of the eye. AQP9 immunolabelling was detected in the nonpigmented ciliary epithelium and retinal ganglion cells. AQP11 immunolabelling was detected in the corneo‐limbal epithelium, nonpigmented ciliary epithelium and inner limiting membrane of the retina. Conclusion: Selective expression of AQP7, AQP9 and AQP11 was found within various structures of the human eye. The detection of these aquaporins in the eye implies a role that may be related not only to water transport but also to the transport of glycerol, lactate and ammonia, with importance for metabolism, especially in the retina.